Leveraging the potential of the German operating room benchmarking initiative for planning: A ready-to-use surgical process data set - Grigory Korzhenevich; Anne Zander (Health Care Management Science, 2024)
We present a freely available data set of surgical case mixes and surgery process duration distributions based on processed data from the German Operating Room Benchmarking initiative. This initiative collects surgical process data from over 320 German, Austrian, and Swiss hospitals. The data exhibits high levels of quantity, quality, standardization, and multi-dimensionality, making it especially valuable for operating room planning in Operations Research. We consider detailed steps of the perioperative process and group the data with respect to the hospital's level of care, the surgery specialty, and the type of surgery patient. We compare case mixes for different subgroups and conclude that they differ significantly, demonstrating that it is necessary to test operating room planning methods in different settings, e.g., using data sets like ours. Further, we discuss limitations and future research directions. Finally, we encourage the extension and foundation of new operating room benchmarking initiatives and their usage for operating room planning.
Keywords: 610; Surgical Process Data; Data analysis; German Perioperative Procedural Time Glossary; Operating Room Benchmarking Initiative; Operating Room Planning; Operations Research